A new species of deep-sea crab of the genus Chaceon Manning & Holthuis, 1989 (Crustacea: Decapoda: Brachyura: Geryonidae) from Western Australia - Davie, P. J.f.; Ng, P. K.l.; Dawson, E. W. (Zootaxa, 2007)
Chaceon albus sp. nov. is described from off Western Australia. It is easily separated from the species with which it has long been confused, C. bicolor Manning, 1989, by proportions of the walking legs, orbital shape, gonopod form and colour. Characters to separate the new species from seven other Indian Ocean species are also discussed.